1993
DOI: 10.1136/gut.34.12.1693
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the histological distribution of insulin like growth factor 1 receptors in the rat gut.

Abstract: The histological distribution of insulin like growth factor 1 (IGF 1) receptors in the rat gut was studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…Efficacy, however, has not been restricted to individual growth factors, and has been reported following oral administration of an extract of growth factors derived from bovine cheese whey [29]. Since receptors for IGF-I are strongly expressed in the intestinal crypts, [31] and exogenously-administered IGF-I has resulted in potent intestino-trophic responses [15,20,21], and mucosal repair [22,25] we investigated the capacity for IGF-I to protect the intestine from damage utilizing a model of chemotherapy-induced intestinal mucositis.…”
Section: Discussionmentioning
confidence: 98%
“…Efficacy, however, has not been restricted to individual growth factors, and has been reported following oral administration of an extract of growth factors derived from bovine cheese whey [29]. Since receptors for IGF-I are strongly expressed in the intestinal crypts, [31] and exogenously-administered IGF-I has resulted in potent intestino-trophic responses [15,20,21], and mucosal repair [22,25] we investigated the capacity for IGF-I to protect the intestine from damage utilizing a model of chemotherapy-induced intestinal mucositis.…”
Section: Discussionmentioning
confidence: 98%
“…The direct action on gut could be supported by the detection of IGF-I and IGF-II receptors covering all of the segments of the gut. 9,27,29 Although in recent years a number of observations led to the theory that the primary actions of IGF-I occured via paracrine or autocrine mechanisms close to the site of its production, IGF-I does have endocrine actions in the circulation.3° This is important because the exogenous e administration of IGF-I in this study depends primarily g on such endocrine actions. Various studies showed I consistently that systemically administered IGF-I can t promote growth, and they demonstrated that IGF-I can 1 leave the circulation and reach important target tissue.31 « In this experiment, the higher total and free plasma « IGF-I concentrations in the IGF group, especially the I latter, may make more IGF-I available to the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…And these immunoreactions were significantly greater in the surface epithelium and crypts in the P group and it decreased in the crypts in E2 group compared to the Ov group. Crypts represent regions of rapid mitosis and differentiation, providing a continual turnover of cells that differentiate into columnar and goblet cells as they migrate from the crypts towards the luminal end of the villi [36,37] . Previous studies also revealed the presence of iNOS immunoreactivity in myenteric neurons, in smooth muscle cells, and in endothelium of the rat duodenum with postembedding immunoelectronmicroscopy [26] .…”
Section: Discussionmentioning
confidence: 99%